Лазарський спів як частина живої обрядової традиції в Македонії - Величковська, Р. (Народна творчість та етнографія, 2009)
The singing on Saint Lazarus day is a still living part of the ritual tradition in the Republic of Macedonia today. We can assert that the entire symbolic complex of these traditional ritual singing forms is consecrated to the family and is linked to the magical element, which function is to secure a good progeny, fertility and a general well-being urged by the power of the ritual. That means that the singing represents a central activity of the ritual group through which is expressed the will of the group and through which at the same time every individual - participant - joins the group. It is before all still an active living means to adhere to the collective ideal, that is, a way of singing expression and also to acquire a well determined social and special cultural position. It means that the process of duration of the ritual singing tradition represents an evident continuity which changes are not far from its older original model still persistent in the less economically developed regions such as the traditional songs and rituals carried out on the eve of Lazarus' Saturday, for example, in the village of Lukè from the Kriva Palanka region (in the north-eastern part of the Republic of Macedonia), and the same genre of songs and processions that are performed in the urban milieus in the Ohrid and Struga regions.